Intraperitoneal chemotherapy following refractory intravenous route in advanced ovarian cancer. - Shafiee MN,; Omar MH,; Suraya A,; Hatta M, (Department of Surgery, UKM Medical Centre, 2013)
Platinum based adjuvant chemotherapy is generally recommended for ovarian cancer to improve the survival rate. Intravenous route is commonly used, easily administered and less associated complications. However, intraperitoneal route is gaining its popularity as a single procedure or adjunctive to the intravenous route. Numerous questions on its eligibility and safety are still perplexed. A case review on a patient with non optimal debulking surgery of advanced ovarian cancer was studied. Intravenous platinum based chemotherapy combined with paclitaxel failed to bring her to clinical remission. Second line chemotherapy, gemcitabin rendered her to poor response with unresolved debilitating ascites needing recurrent drainage. Surprisingly, a trial of intraperitoneal chemotherapy with cisplatin revealed a great response with a complete clinical remission.